2021
DOI: 10.1108/maj-09-2020-2830
|View full text |Cite
|
Sign up to set email alerts
|

Internal audit quality and earnings management: evidence from the UK

Abstract: Purpose This study aims to examine the association between internal audit quality and the involvement of UK companies in earnings management practices. Design/methodology/approach To measure the internal audit quality, this study uses 115 responses for a postal questionnaire that was addressed to the heads of internal audit departments in a sample of non-financial listed companies in the UK context. The other financial and governance data for the respondent companies were collected from the Datastream and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 75 publications
(141 reference statements)
0
20
0
6
Order By: Relevance
“…Kaawaase et al (2021) tried to provide the association among corporate governance roles, IAQ and the quality of financial reports in Uganda's financial entities and found out that either board attributes and IAQ are quite related to better financial reports. Ismael & Kamel (2021) investigated the relationship between IAQ and United Kingdom firms in earnings management procedures and demonstrated the consistent role of IA in diminishing the incidence of atypical accruals, corroborating the negative relation amid IAQ and earnings management. Krichene & Baklouti (2021) tried to figure out the approaches of internal auditors on IAQ and to emphasize their contrasting characteristics considering their impressions of IAQ antecedents and demonstrated that features as the internal auditors' expertise, reporting autonomy, conformity with IPPF, liaison with the external auditors, internal auditors' private affinities, admission to data and area of activity presents a positive relation with IAQ in various levels of significance.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Kaawaase et al (2021) tried to provide the association among corporate governance roles, IAQ and the quality of financial reports in Uganda's financial entities and found out that either board attributes and IAQ are quite related to better financial reports. Ismael & Kamel (2021) investigated the relationship between IAQ and United Kingdom firms in earnings management procedures and demonstrated the consistent role of IA in diminishing the incidence of atypical accruals, corroborating the negative relation amid IAQ and earnings management. Krichene & Baklouti (2021) tried to figure out the approaches of internal auditors on IAQ and to emphasize their contrasting characteristics considering their impressions of IAQ antecedents and demonstrated that features as the internal auditors' expertise, reporting autonomy, conformity with IPPF, liaison with the external auditors, internal auditors' private affinities, admission to data and area of activity presents a positive relation with IAQ in various levels of significance.…”
Section: Introductionmentioning
confidence: 75%
“…The internal audit function (IAF) can be considered independent if its practices adhere to standards internationally accepted, as well as its activities are performed autonomously, due both to the adjustment of the level of reporting to senior management and the timely issuance of reports to the Board of Directors (IIA, 2013). The IAF is believed to be a governance branch and, when effective, is widely believed to conduct distinct significant roles during the process of financial reporting (Ismael & Kamel, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Logistic regression was performed as described by Purba et al (2021). The least-squares method was used by Ismael and Kamel (2021), Bhutta et al (2021), andChakroun et al (2022, pp. 331-362).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vidaus audito kokybę ir pajamų valdymo ryšį tiriantys mokslininkai (Ismael et al, 2021) teigia, kad įmonės turi daugiau dėmesio skirti vidaus audito kompetencijos stiprinimui, kad sumažintų oportunistinį vadovybės elgesį. Yildiz ir Yilmaz (2020) nuomone, vidaus auditorių profesinė kompetencija, charakteris ir motyvacija yra labai svarbūs, kad vidaus auditas suteiktų pridėtinę vertę organizacijai.…”
Section: Tradicinės Vidaus Audito Veiklos Ir Jų Plėtra Bei įTaka Pridėtinės Vertės Kūrimuiunclassified